Modern philosophy : the seventeenth and eighteenth centuries - Francks, Richard (Fundamentals of philosophy (London, England), 2003)
This introductory text for students gives a thematic survey of the ideas of the major philosophers of the 17th and 18th centuries. Topics include Perception And Ideas, Matter And Motion, Necessity And Freedom, And Minds and persons.